Analisis Kebutuhan Air Irigasi di Lahan Pertanian Distrik Muara Tami, Kota Jayapura - paseru, riswandy loly; Jansen, Davy Ivan Robert (Universitas Teuku Umar, 2024)
Food is one of the most basic needs for human existence. Food is a source of maintaining a person's health. In order to raise the standard of public health, the populace must routinely eat fulfillment, a basic need. To attain food self-sufficiency, there must be a corresponding rise in food production with population growth. The supply of irrigation water for food production must be balanced with the growth in food output. Utilizing water resources from Tami Dam, agricultural land with an irrigation area of 5000 Ha is located in East Koya and West Koya, Muara Tami District, Jayapura City. In order to ensure that there is enough water for every acre of agricultural land that is irrigated by irrigation water channels, irrigation water needs must be taken into account. To address a number of water-related issues that could become uneven, the requirement for irrigation water for food production must be taken into account. The methodology employed in this study begins with the collection of climatological data, followed by an analysis of percolation rates, an analysis of evaporation using the Penman method, an analysis of evapotranspiration using the Modified Penman method, an analysis of the water requirements for soil processing, and an analysis of the water requirements for rice plants. According to the study's findings, the Muara Tami District's maximum evapotranspiration (Eto) demand over the previous ten years was 7.22 mm/day, or 0.84 ltr/sec/ha. The Muara Tami District has a mandated irrigation water requirement (DR) of 1.99 ltr/sec/ha.